SERVICE LEARNING IN STRENGHTHENING INNOVATION, AUTHENTICITY, AND BRANDING OF HONEY PRODUCTS AT B-B TOWN SDN. BHD., MELAKA, MALAYSIA - Satriadi Satriadi; Armansyah; Tubel Agusven; Ratna Putri Nilasari; Irmawati Irmawati; Mai Yuliza (PT. Jurnal Center Indonesia Publisher, 2026)
This service-learning activity was conducted to address the challenges faced by the local business Rumah Madu in Melaka, Malaysia, specifically in maintaining product authenticity, developing innovation, and strengthening branding strategies amidst global market competition. The solution implemented involved a service-learning approach through instructional sessions and direct observation with business managers to understand the production process, marketing strategies, and quality management practices. The purpose of this activity was to identify innovation and branding practices rooted in the authenticity of local products, as well as to provide academic contributions through the application of management theories in real MSME contexts. This program also contributed to the partner by preparing business development recommendations based on innovation and digital marketing. The findings reveal that product innovation utilizing local bee biodiversity, the implementation of ISO-standard quality systems, and the use of digital media have strengthened the brand image and competitiveness of Rumah Madu. This experience demonstrates that service learning serves as an effective approach in bridging academic learning with the enhancement of local business capacity in a sustainable manner.